Assessment of molasses products containing additives to reduce methane emissions from beef cattle - Nikoloric, Maria; Simanungkalit, Gamaliel; Possell, Malcolm; González, Luciano Adrián; Chaves, Alex V. (Frontiers in Animal Science, 2025)
Methane (CH4) emissions from ruminants significantly contribute to agricultural greenhouse gases. Strategies to reduce these emissions without compromising productivity are urgently needed. This study evaluated the effectiveness of a novel product incorporated into molasses containing additives and grain-based pellets to reduce CH4 emissions and improve productivity in beef cattle. Four products were screened in vitro for their efficacy in reducing CH4 production. The most effective (Product 3) was then incorporated into grain-based pellets and offered to steers via GreenFeed units at target intakes of 0, 100, and 200 g/head per day. Dry matter intake (DMI), CH4 production, CH4 yield (g CH4/kg DMI), CH4 intensity, water intake, and average daily gain (ADG) were measured. Product 3 reduced in vitro CH4 production by over 90% at a 6% inclusion rate (P < 0.05). In vivo study, steers supplemented with product-containing pellets tended (P=0.07) to reduce CH4 production by 10.7% compared to the control. Methane yield was reduced (P < 0.01) by 11.7% and 7.5% for the 100 and 200 g/day supplementation levels, respectively. Methane intensity tended (P=0.06) to be 16.8% lower in supplemented groups. Product intake was negatively correlated with CH4 yield and intensity and positively associated with water intake and ADG (P < 0.05). The inclusion of Product 3 in supplements beef cattle fed high forage diet significantly reduced methane yield and tended to reduce CH4 production and intensity, without negatively impacting performance. Product 3 shows potential as a viable CH4 mitigation strategy for high forage diet systems. However, further research is needed to assess the long-term effects and potential microbial adaptation associated with higher or prolonged dosing.